Flow cytometric 96‐well microplate‐based in vitro micronucleus assay with human TK6 cells: Protocol optimization and transferability assessment. (27th February 2013) - Bryce, Steven M.; Avlasevich, Svetlana L.; Bemis, Jeffrey C.; Tate, Matthew; Walmsley, Richard M.; Saad, Frédéric; Van, Kris; De, Marlies; Van, Freddy; Lukamowicz‐Rajska, Magdalena; Elhajouji, Azeddine; Dertinger, Stephen D.
<x xml:space="preserve">Abstract</x> An automated approach for scoring in vitro micronuclei (MN) has been described in which flow cytometric analysis is combined with compound exposure, processing, and sampling in a single 96‐well plate (Bryce SM et al. [2010]: Mutat Res 703:191‐199). The current report describes protocol optimization and an interlaboratory assessment of the assay's transferability and reproducibility. In a training phase, the methodology was refined and collaborating laboratories were qualified by repeatedly testing three compounds. Second, a set of 32 chemicals comprised of reference genotoxicants and presumed non‐genotoxicants was tested at each of four sites. TK6 cells were exposed to 10 closely spaced compound concentrations for 1.5‐ to 2‐cell population doublings, and were then stained and lysed for flow cytometric analysis. MN frequencies were determined by evaluating ≥5, 000 cells per replicate well, and several indices of cytotoxicity were acquired. The prevalence of positive results varied according to the MN‐fold increase used to signify a genotoxic result, as well as the endpoint used to define a cytotoxicity limit. By varying these parameters, assay sensitivity and specificity values ranged from 82 to 98%, and 86 to 97%, respectively. In a third phase, one laboratory tested a further six genotoxicants and five non‐genotoxic apoptosis inducers. In these experiments assay specificity was markedly improved when top concentration selection was based on two cytotoxicity endpoints—relative survival and quantification of ethidium monoazide‐positive events. Collectively, the results indicate that the miniaturized assay is transferable across laboratories. The 96‐well format consumes considerably less compound than conventional in vitro MN test methods, and the high information content provided by flow cytometry helps guard against irrelevant positive results arising from overt toxicity. Environ. Mol. Mutagen. 54:180–194, 2013. © 2013 Wiley Periodicals, Inc.